Intramuscular Transplantation of Myogenic Cells in Primates: Importance of Needle Size, Cell Number, and Injection Volume. Issue 1 (February 2014) - Skuk, Daniel; Goulet, Marlyne; Tremblay, Jacques P.
The aim of this study was to quantitatively define the main measurable technical parameters for the intramuscular transplantation of myogenic cells in primates. Myoblasts transduced with the gene coding for β-galactosidase were injected into the skeletal muscles of 15 monkeys. The following parameters were studied: needle size, number of cells per injection, and volume of cell suspension per injection. Monkeys were immunosuppressed with tacrolimus. The cell-injected sites were biopsied 1 or 2 months later. Biopsies were examined histo logically to assess the myoblast engraftment and the muscle structure. The conclusions were as follows: (1 ) Needles should be thin enough to avoid important tissue damage and allow muscle regeneration as satisfactory as possible. Among those tested, 27G should be the choice if the length is consistent with depth of injection. (2 ) At least 100, 000 cells should be delivered per centimeter of needle trajectory. (3 ) The smallest volumes of cell suspension per injection should be used. In this study, 1 μl/cm of injection trajectory was sufficient. In principle, these parameters apply to muscles in which no damage occurred other than the injections.